PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS KOMPUTER DENGAN PENYAJIAN MATERI BERBASIS MASALAH PADA MATERI POKOK SISTEM KOORDINAT KELAS VIII SMP/MTs - Supri Hartini; Nahor Murani Hutapea; Yenita Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This-research aims to-develop interactive multimedia using a-problem based learning design on coordinate system topic for 8th grade students. The background of this research was development of information and communications technologies which have made some impact on the practice of education and that limited teacher preparation for the use of ICT in teaching/learning process. The research was conducted to provide learning media that can be directly use in Problem Based Learning (PBL). This research used ADDIE development model by Dick-and Carry. Development is done through the following steps:-(1)-Analyze; created a-need analysis, identified problem (needs)-of-the-students;-(2)-Design; drew a-storyboard which presented the contents of the display of interactive multimedia, prepared everything that will be required among the creation of the media;-(3)-Development; made the media on the computer based on the storyboard that has been design;-(4) Implementation and Evaluation; tested the learning media and analysis the result. The research instrument used is validation sheet to assess the validity requirement of learning media and practicality instrument which is in the form of questionnaire of student response toward learning media implementation. The learning media validated by three-validators, then practicality test was-conducted in MTs-Darul-Hikmah Pekanbaru which is tested in a small-group and large-group. Based on the data analysis, the-result showed that interactive multimedia using a-problem-based-learning design on coordinate-system topic belong to the category of very-valid with an-average value is 3.89 and also could be used very well as learning media for 8th grade-students. Recommendation-for-further research is to test the media in learning process to observe the-effect-of-this-learning-media-to-increase-student’s-score-(learning-outcomes).Key Words : Interactive Multimedia, Development, Coordinate System